Rural Poverty Reduction in Northeast Brazil : Achieving Results through Community-Driven Development - Coirolo, Luis; Lammert, Jill (World Bank, Washington, DC, 2012)
Over the past two decades, Brazil has been employing a very innovative community-driven development (CDD) approach to reducing rural poverty in its Northeast region. These efforts began with a relatively small pilot in the late 1980s, which was then extended to the entire Northeast region in the early 1990s. Emboldened by early results on the ground, the state and Federal governments have since continued to steadily scale up this CDD program, known in Brazil as the Programa de Combate a Pobreza Rural (PCPR, or by its English acronym of RPRP, Rural Poverty Reduction Program), to the point where it is now reaching some 11 million people. The process has been one of continual piloting, refinement and expansion, underpinned by very active monitoring and evaluation efforts by the government itself, the World Bank as the primary external partner, foreign and local non-governmental organizations (NGOs) and academics.